Case Report: Blastic plasmacytoid dendritic cell neoplasm mimicking systemic lymphoma: a multidisciplinary diagnostic challenge - Baixue Lv; Qin Rong; Yan Li; Dongdong Zhang (Frontiers in Medicine, 2026)
Background Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is an aggressive hematologic malignancy originating from plasmacytoid dendritic cell precursors. While classic cases present with prominent cutaneous nodules and lymphadenopathy, predominant generalized lymphadenopathy can obscure the diagnosis, frequently resulting in a misdiagnosis of systemic lymphoma. Case presentation A 56-year-old male presented with a one-month history of generalized pruritic erythema and multi-regional lymphadenopathy. Initial PET-CT demonstrated systemic lymphadenopathy and splenomegaly with increased metabolic activity, mimicking lymphoma. To establish a definitive diagnosis, integrated biopsies of the skin, bone marrow, and inguinal lymph nodes were performed. Bone marrow cytology revealed that unidentified cells accounted for 7% of the total nucleated cells. Immunohistochemical analysis revealed neoplastic cells positive for CD123, CD4, CD56, TCF4, and TCL1, confirming the diagnosis of BPDCN. The patient achieved complete remission (CR) after two cycles of induction chemotherapy with the DA (daunorubicin and cytarabine) regimen, followed by successful consolidation via allogeneic hematopoietic stem cell transplantation (allo-HSCT). At the 4-month post-transplant follow-up, the patient remains in stable remission with no evidence of disease recurrence. Conclusion This report details a BPDCN presentation that closely mimics systemic lymphoma. A definitive diagnosis hinges on the integration of multi-site histopathological analysis and comprehensive radiographic findings. Early diagnostic precision is paramount for the timely initiation of intensified therapeutic strategies, such as allo-HSCT, which remain the cornerstone for improving long-term survival in this recalcitrant malignancy.